Menu Differentiation Strategy as a Culinary Tourism Attraction: A Qualitative Descriptive Approach - Mulia, Satrio Nata; Lesmana, Fanji; Ramadhanty, Annisa (International Journal of Business, Law, and Education, 2026)
The rapid expansion of the culinary tourism industry has generated intense competition and increasing product homogeneity, compelling food and beverage (F&B) businesses to formulate effective menu differentiation strategies in order to create distinctive value propositions. This study aims to describe the forms of menu differentiation strategies and analyze their role in enhancing tourist attraction in Bandung and Malang. Employing a descriptive qualitative approach with a phenomenological method, this research explores the essence of tourists’ lived experiences through participatory observation, in-depth interviews, and triangulation using digital perception analysis derived from Google Reviews and social media platforms. The findings indicate that effective menu differentiation integrates three interrelated dimensions: physical aspects (uniqueness of taste and ingredients), interactional aspects (service quality and hospitality), and emotional aspects (historical and cultural narratives embedded in the menu). Google Reviews function as an objective performance mirror that validates service consistency, while social media operates as a platform for social identity construction and visual storytelling, particularly among Generation Z consumers. The study concludes that the success of differentiation strategies depends significantly on the ability of businesses to transform menu uniqueness into shareable digital content, thereby creating memorable gastronomic experiences and strengthening tourist loyalty.